Awwaliyah Madrasah Diniyah Compulsive Education Policy for Elementary School Students (Multicase Study in Indramayu and Kuningan Regencies, West Java) - Umar Sidiq; Mukhibat Mukhibat (AL-ISHLAH: Jurnal Pendidikan, 2022)
There are regulations from the Regional Governments of Indramayu and Kuningan Regencies to require SD/MI students to attend the first madrasa program. Furthermore, this study examines the process of establishing and sustaining regional regulations (Perda). This research is a case study with a multi-case design. Therefore, a qualitative approach is appropriate in conducting this research. In-depth interviews, participant observation, and documents were used to collect data. In addition, data reduction, data display, and verification are used in the data analysis process. To ensure the validity of the data analysis, the researcher rechecked the data through credibility, transferability, dependability, and suitability. The results showed that (1) Perda no. 2 of 2003 comes from the government's religious politics to minimize social ills. Meanwhile, the existence of Regional Regulation No. 2 of 2008 was influenced by social engineering as a consequence of the formulation of the first madrasa law and was later funded by the government (2) Top-down and bottom-up theory integrated with a participatory approach was applied to investigate the First Madrasah Aliyah Education Policy strategy. Participation of the community, government, and members of the parliamentary education commission get together to involve religious education and regional development. There are three steps in carrying out the implementation; the stages of formulation, legislation, implementation and control of local regulations.